Wady wrodzoneTotal transposition of the great arteries with ventricular septal defects in a premature newborn with birth body weight of 1400 g. A report of successful treatment - Skalski, Janusz H.; Mroczek, Tomasz; Kordon, Zbigniew; Kania, Urszula; Mitkowska, Zofia; Rudziński, Andrzej; Pypłacz, Dariusz; Kołcz, Jacek; Dudyńska, Mirosława; Pietrzyk, Jacek J. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The report describes the course of a successful treatment of a low birth body weight (1400 g) premature newborn with total transposition of the great arteries, concomitant multiple ventricular septal defects and patent ductus arteriosus. The surgical treatment was delayed, employing a continuous prostaglandin E1 infusion. When 13 days old, the newborn was subjected to Rashkind balloon septostomy (at that time, the body mass was 1340 g). When the child was 70 days old (chronological age of 10/52; corrected age of 2/52) and his body mass was 2450 g, he was subjected to an anatomical correction of the defect (an arterial switch operation). The postoperative course was favourable. Seven months following the operation, the child is developing harmoniously, and no abnormalities involving the circulatory system or neurological disturbances are seen.